Efficacy and safety of treatment with human insulin analogues in daily management of insulin naive patients with type 2 diabetes mellitus: results of multicenter 52-week observational study A1chive - Marina Vladimirovna Shestakova (Endocrinology Research Centre, 2012)
Modern insulin analogues allow safe improvement of glycemic control (not accompanied with increase in body mass or rate of severe hypoglycemic events) and its efficient maintenance during long period of time. In this paper we present results of multicenter 52-week prospective observational study A1chive (Russian cohort, n=9342), designed to assess safety and efficacy of treatment with human insulin analogues (Levemir?, NovoMix? 30 and NovoRapid? (Novo Nordisk) in daily management of insulin naive patients with type 2 diabetes mellitus. Prescription of human insulin analogues resulted in clinically and statistically significant improvement of glycemic control irrespective of initial insulin regimen. Therapy by various regimens (Levemir?, NovoMix? 30 or Levemir? + NovoRapid?) under conditions of daily clinical practice leads to marked improvement in glycemic control as measured by HbA1c (-2.9% in 12 month) with no evidence for negative influence on tolerability and short-term safety of the treatment. Furthermore, decrease in HbA1c levels was associated with pronounced and stable decrease in fasting and postprandial glucose levels (-5.0 mmol/L and -5.7 mmol/L, respectively). By the end of the follow-up all regimen groups reported improvement of QoL by treatment satisfaction criterion.